VOCABULARY-ORIENTED FLASHCARDS AS A SOLUTION TO THE LACK OF GERMAN USAGE IN DAILY LIFE: PROJECT WORK IN THE PROJECT SECTION OF THE "SEMINAR IN GERMAN" COURSE AT THE GERMAN DEPARTMENT OF KHON KAEN UNIVERSITY - Suwanthikarn, Sasiwimol (Pattimura Excellence Journal of Language and Culture, 2024)
The exchange of experiences regarding the challenges of learning German with the students in the "Seminar in German" course in the second semester of 2024 at Khon Kaen University revealed that the lack of opportunities to practice the German language in daily life is the major shared challenge. The students were divided into groups to brainstorm possible solutions to this issue, and each group was tasked with creating a project that would produce an end product enabling as many opportunities as possible to practice German in everyday situations. The projects were presented at the end of the semester and tested by the class and the instructor to see how effectively they worked. The students were divided into five groups, and each group created a different end product. This article will focus on the project work of the students in Group 3, namely flashcards on vocabulary related to different everyday topics. The reason for this focus is that this is my first article in which I write about the project works from this course. I see vocabulary as the foundation of language learning, which is why I want to begin by discussing the vocabulary-oriented project work. These flashcards were designed to help learners remember words related to specific topics and to form sentences using them. The students and their target audience were at the A2 language level. Nevertheless, the creation of language games in areas they wish to practice, in a form that matches their interests and is playful, can be adapted and applied to learners of all language levels.